The illocutionary profile of text units with purpose semantics in the aspect of their modeling and interpretation - L.V. Voronina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The illocutionary complex that determines the pragmatic meaning of text units with purpose semantics as part of the question-answer dialogue was analyzed. Using the methods of conversation analysis, introspection, linguistic modeling and observation, a multifarious analysis of the adjacent pairs in the political interview and talk show fragments was carried out. The factors that define the generation of purpose-related judgments and the choice of indirect ways to convey the communicative intentions of the addresser were singled out, as well as the aspects that are important for understanding the perceived content by the addressee. The organization of the communicative continuum within the framework of interaction was investigated. The functionality of the pragmatic context (the background of spoken interaction) was revealed. The factors influencing the quality of the illocutionary profile of text units (clarity/blur) as it is perceived and interpreted by the addressee were established. The signals of the communicative intentions generated by the addresser were considered. The choice of spoken response in the situations of harsh pressure was discussed. It was demonstrated that the pragmatic context plays a leading role in perceiving of the illocutionary complex during the communicative interaction.